How to solve 6x + 1 = 13? Get the answer and stepwise instruction to solve linear equation in one variable 𝒙.

#### Steps for finding the solution

We have 6**x** + 1 = 13

First, we move the *non ***x** terms to the RHS of the equation. To do this, we subtract 1 from both sides.

**Note: ** if a = b, then a - c = b - c

Therefore, 6**x** + 1 - 1 = 13 - 1

or, 6**x** = 12

Next, divide both sides by 6, which is the coefficent of **x**

**Note: ** if a = b, then a ÷ c = b ÷ c

6**x**/6 = 12/6

**x** = 12/6

To simplify, divide both numerator and denominator by 6, which is the GCF of 12 and 6:

**x** = 2/1 or, **x** = 2